(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
Postharvest grain losses, particularly for staple crops, are a significant challenge to food security in Nigeria, with losses estimated between 20% and 35%. This study examined the factors influencing the adoption of improved postharvest storage technologies (IPSTs) among grain traders in Ilorin metropolis, Kwara State, Nigeria. A two-stage sampling technique was employed to select 229 respondents from four major grain markets in Ilorin, Nigeria. Data were collected through a structured interview schedule and questionnaire as the instrument. Analysis involved both descriptive and inferential statistics, with binomial logistic regression identifying key factors influencing technology adoption. The results showed that grain traders had an average age of 45, with men (77.3%). The majority of the respondents were married (81.8%) and had primary education (51.8%). They had an average of 13 years in the grain trade and earned an average weekly income of ₦250,000 (166). The majority (98.2%) were aware of improved postharvest storage technologies, with the usage of Purdue Improved Crop Storage (PICS) bags (51.5%) ranking first. Grain-based associations were the main source of information on awareness of IPSTs among respondents. The perceived benefits of IPSTs, starting with the most important, included improved grain quality, extended shelf life, and reduced pest infestation with a mean score of 4.39, 4.13, and 4.08, respectively. Binomial logistic regression indicated that education, association membership, access to credit, and income significantly influenced the usage of IPST among grain traders in the study area. The study recommends improving access to credit, enhancing training, and strengthening trade associations to promote IPST usage and reduce postharvest losses.